Trust, distrust, and open‐book accounting in three client‐vendor relationships - Agndal, Henrik; Nilsson, Ulf (Contemporary Accounting Research, 2024)
Abstract Extant management accounting research has conceptualized the interplay between trust, distrust, and open‐book accounting (OBA) as a relationship‐level phenomenon, largely ignoring that inter‐organizational relationships are often complex entities that comprise multiple arenas of exchange where (dis)trust and OBA can interact in different—and potentially contradictory—ways. To address this theoretical oversight, we draw on relational exchange theory to propose that (dis)trust largely forms within OBA domains where different forms of data are exchanged for different purposes. Trust and distrust may thereby coexist within a relationship. We also propose that (dis)trust spills over to influence the conditions for OBA in other domains. Consequently, trust and distrust not only take shape in cumulative processes within OBA domains but also diffuse between domains in a relationship. Empirical observations from a longitudinal case study of a retail buyer's attempts to introduce OBA in three vendor relationships lead us to suggest that competence‐trust spillover is determined largely by domain similarity, while goodwill‐trust spillover relies to a greater extent on staff mobility between OBA domains. Overall, the negative effects of distrust spillover on the implementation of OBA appear greater than the positive effects of trust spillover. Our study shows that, by analyzing the domain‐specific nature of trust and distrust, future research can increase our understanding of the relationship between data characteristics and (dis)trust, as well as explain how trust and distrust interact to determine conditions for data exchange between organizations.